2006
DOI: 10.1039/b605251g
|View full text |Cite
|
Sign up to set email alerts
|

DNA as a supramolecular scaffold for the helical arrangement of a stack of 1-ethynylpyrene chromophores

Abstract: A highly organized helical pi-stacked arrangement of 1-ethynylpyrene moieties along the major groove of duplex DNA can only be achieved if more than three chromophores have been synthetically incorporated adjacent to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 17 publications
0
61
1
1
Order By: Relevance
“…We have obtained a similar sequence of CD signals for the assembly of covalently attached pyrenes in the major groove of duplex DNA. [14,15] It is assumed that the right-handed sense of the helical conformation of the DNA around the PB dimers in DNA1 and DNA3 forces the PB chromophores in both duplexes to aggregate by following the sense of the right-handed helix. Moreover, the similarities in the shapes of the CD signals for DNA1/DNA3 and DNA6 indicate a right-handed helical arrangement of the six PB chromophores also in DNA6, but not in DNA5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have obtained a similar sequence of CD signals for the assembly of covalently attached pyrenes in the major groove of duplex DNA. [14,15] It is assumed that the right-handed sense of the helical conformation of the DNA around the PB dimers in DNA1 and DNA3 forces the PB chromophores in both duplexes to aggregate by following the sense of the right-handed helix. Moreover, the similarities in the shapes of the CD signals for DNA1/DNA3 and DNA6 indicate a right-handed helical arrangement of the six PB chromophores also in DNA6, but not in DNA5.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that a helical and regularly structured p array of 1-ethynylpyrene groups that have been covalently attached to the 5-position of uridines can only be formed if more than three chromophores are placed adjacent to each other. [14] Similar DNA systems with five adjacent pyrene-modified uridine units showed a remarkably strong fluorescence enhancement, which is sensitive to DNA base mismatches and thermal denaturation of the duplex. [15] DNA duplexes that have been functionalized by a helical stack consisting of five adjacent chromophores with mixed pyrene-modified or phenothiazine-modified uridine sequences show a modulated fluorescence readout.…”
Section: Introductionmentioning
confidence: 99%
“…This would be in line with an observation made in ref. [18]. There DNA double- helices have been synthesized that have an increasing number of pyrene units (attached via an acetylene spacer to uracil) in adjacent positions.…”
mentioning
confidence: 99%
“…3 Thereby the primary stacking interactions and chirality can be controlled. [9][10][11][12] In the latter case, mainly pyrenes, 10 nile reds 11 and porphyrins 12 were attached covalently to DNA bases via short and rigid ethynyl bridges. [9][10][11][12] In the latter case, mainly pyrenes, 10 nile reds 11 and porphyrins 12 were attached covalently to DNA bases via short and rigid ethynyl bridges.…”
mentioning
confidence: 99%
“…10,15 Especially the band at 408 nm rises upon formation of the PyRdU assembly along (dA) 17 by cooling down to sample (Fig. The UV/Vis spectrum of the PyRdU assembly in the presence of (dA) 17 exhibits the ethynyl pyrene-typical fine structure with absorption bands at 384 nm and 408 nm.…”
mentioning
confidence: 99%